Increase of physical capacity of children with congenital clubfoot by means of physical rehabilitation - Mikhailova N.E (Kharkov National Pedagogical University, 2012)
The aim is to study the effect of rehabilitation on physical performance of children with congenital clubfoot. The study involved 68 preschool children with congenital clubfoot and 34 healthy children. The data on the level of physical performance in preschool children. Substantiated directions and conditions of the physical rehabilitation of congenital clubfoot. Defined starting and controlling the level of physical performance in preschool children. The results obtained prove the effectiveness of physical rehabilitation to improve physical performance in children with congenital clubfoot.